Implementasi Mobile Commerce Untuk Meningkatkan Pendapatan Anggota Koperasi Gentiaras Pringsewu - Andreas Andoyo; Siti Mukodimah; Andino Masaleno (Institut Bakti Nusantara, 2020)
Mobile commerce application is one of the types of electronic commerce that has benefits for online sales and marketing systems. The internet in general, has been used by the public as a means of information and is used as a business tool to market a particular product. In an effort to increase the added value and sale of products produced by members of the Gentiaras cooperative, a digital platform has been built under the name Olshop PSW which has the function of matching and promoting the products of the members of the Gentiaras Pringsewu Cooperative. This application was built using the Systems Development Life CycleI Method using PHP and Java programming languages and database design using Mysql.